PENYELENGGARAAN BIMBINGAN KONSELING DI SEKOLAH DASAR - Tanod, Mareyke Jessy; Diswantika, Noviana; Iasha, Vina (Jurnal Pendidikan Dasar, 2019)
This paper is the result of a qualitative descriptive study that aims to find out empirical evidence about the implementation of guidance and counseling at Bakung 1 Elementary School in Bandar Lampung. The results of the study show that the implementation of guidance and counseling refers to the results of understanding of students. The strategies applied by classroom teachers consist of integrating guidance and counseling material into the subject matter, choosing the right method and media, remedial, building empathic communication, setting an example, appreciating and strengthening, identifying and choosing assistance programs, and transfer of hands. Class teacher competence still needs to be improved so that the implementation of guidance and counseling in Elementary Schools can be programmed well.